Harnessing benefit from targeting tumor associated carbohydrate antigens - Thomas Kieber-Emmons; Behjatolah Monzavi-Karbassi; Laura F. Hutchins; Angela Pennisi; Issam Makhoul (Taylor & Francis Group, 2017)
Integrating additive or synergistic antitumor effects that focus on distinct elements of tumor biology are the most rational strategies for cancer treatment. Treatments for breast cancer have increased overall survival, but remain limited by lack of efficacy in a subset of breast cancer patients. The real challenge is to define what elements of tumor biology make the most sense to be integrated. An emerging strategy is to consider a systems biology approach to impact multiple interactions in networks as compare with hitting a specific protein-protein interaction target. In this review, we consider how targeting tumor associated carbohydrate antigens (TACA) that are fundamental to signal pathways might be tailored to harness benefit from combination therapy of sustained immunity with chemotherapy. An approach we are developing makes use of a carbohydrate mimetic peptide (CMP) to induce polyspecific antibodies, which by their nature have numerous on and off target effects. Linking multi-target TACA recognition with mechanisms affecting tumor growth in the context of network heterogeneity and concepts of immune surveillance to tumor cells and the type of breast cancer patients that would benefit from such an approach provides a novel integrative treatment.